2008
DOI: 10.1007/s10669-007-9160-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and social impacts of electricity utilization: broadening the debate

Abstract: Exposure of small laboratory animals to powerfrequency high-voltage electric fields was reported to have endocrinological effects, including changes in pineal melatonin levels. It has been assumed that these results are directly attributable to electric-field effects, but this article suggests that air ionization, produced by corona activity at the animals' body surfaces, may have been biologically active and could be relevant to the interpretation of some epidemiological and other studies. Although presently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Extending epidemiological considerations to include lower-voltage overhead powerlines, rather than the high magnetic field producing, high voltage lines presently considered would lead to conclusions contrasting sharply with those expressed by Schmeidel and Blettner (Schmiedel and Blettner 2010) that “the public health impact is low”. The “Kaiser Permanente Medical Care Program” (KP) population in California studied in the report by Li et al (2011) was originally defined by Li et al (2002) who noted that maximum magnetic field exposure levels were comparable with those found in a nationwide survey (Zaffanella and Kalton 1998) which associated high magnetic field exposure at home with close residential proximity to overhead powerlines (page 6-9, and see page A-56).…”
Section: Resultsmentioning
confidence: 87%
“…Extending epidemiological considerations to include lower-voltage overhead powerlines, rather than the high magnetic field producing, high voltage lines presently considered would lead to conclusions contrasting sharply with those expressed by Schmeidel and Blettner (Schmiedel and Blettner 2010) that “the public health impact is low”. The “Kaiser Permanente Medical Care Program” (KP) population in California studied in the report by Li et al (2011) was originally defined by Li et al (2002) who noted that maximum magnetic field exposure levels were comparable with those found in a nationwide survey (Zaffanella and Kalton 1998) which associated high magnetic field exposure at home with close residential proximity to overhead powerlines (page 6-9, and see page A-56).…”
Section: Resultsmentioning
confidence: 87%
“…3 Groom and Chalmers noted that in conditions of high atmospheric humidity, corona discharge from 132-kV transmission lines originated at transmission tower line support insulators, as surface moisture reduced the effective line-to-ground distance, increasing local electric field strength and thus the probability of corona action. 4 Residential proximity to such discharge sites could increase the risk of possible adverse health impacts from exposure to airborne bioactive discharge products.…”
mentioning
confidence: 99%
“…Most studies of adverse health impacts, apparently associated with exposure to the electricity utilization environment, have been concerning electric and magnetic fields, but it has been suggested that other aspects of the utilization environment should now be considered: in particular, the role of direct biological activity by airborne products of corona action at electrically energized structures. 3 Groom and Chalmers noted that in conditions of high atmospheric humidity, corona discharge from 132-kV transmission lines originated at transmission tower line support insulators, as surface moisture reduced the effective line-to-ground distance, increasing local electric field strength and thus the probability of corona action. 4 Residential proximity to such discharge sites could increase the risk of possible adverse health impacts from exposure to airborne bioactive discharge products.…”
mentioning
confidence: 99%
“…This model assumes that biologically active airborne byproducts of electrical corona discharge/arcing (Franklin and Harland 1974;Pethig 1983;Kroling 1985) may be produced at supply line surface irregularities and/or exposed connections on overhead equipment such as insulators, pole-mounted transformers, etc. Broader aspects of this model have been elaborated elsewhere (Sidaway 2008).…”
Section: Introductionmentioning
confidence: 99%